Solid waste generation In Selangor during the covid-19 pandemic (2019-2021) - Mohd Daud, Nurul Iman; Ahmad Tajuddin, Husna; Nordin, Noor Faizul Hadry; Mansor, Mariatul Fadzillah (IIUM Press, International Islamic University Malaysia, 2024)
Selangor, like many other Malaysian states, experienced various disruptions due to the pandemic. In addition to health and economic challenges, the populous state also faced notable issues regarding waste production. The COVID-19 pandemic has led to a dramatic rise in solid waste generation, especially in its two largest sources, municipal solid waste (MSW) and clinical solid waste (CSW). The pandemic resulted in people staying at home and relying on home deliveries, which led to an escalation in MSW. Healthcare workers also faced longer hours due to the growing number of COVID-19 patients, causing increased production of CSW. However, it is unclear which waste source is more affected by the pandemic. In the present study, the trend of solid waste generation in Selangor during the pandemic was investigated. A comparison was also made between the annual generation rates of both MSW and CSW, particularly spanning the period from 2019 to 2021. The findings showed that in 2019, Selangor witnessed a generation of 1,358,786 tonnes of MSW, which increased to 1,426,551 tonnes in 2020 and further escalated to 1,484,282 tonnes in 2021. As for CSW, Selangor generated a total of 7,343 tonnes in 2019, 9,703 tonnes in 2020, and 12,993 tonnes in 2021. The analysis uncovered that MSW exhibited an average annual generation rate of 4.5%, whereas CSW demonstrated a higher generation rate of 33%. An upward trend was seen in both MSW and CSW generation in Selangor